Biologi Reproduksi dan Faktor Kondisi Ikan Tiger Barb (Puntigrus partipentazona) di Perairan Danau Toba - Novi Kristina Sinabutar; Agung Setia Batubara (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
The increasing occurrence of introduced fish species in Lake Toba highlights the need to investigate their reproductive biology and condition factor to understand their invasive potential. This study aimed to analyze the reproductive biology and condition factor of Tiger Barb (Puntigrus partipentazona) in Lake Toba. The study was conducted from January to March 2026 at three sampling stations in Pangururan District using a survey method with purposive sampling. Data were collected through fish trapping using fish traps, water quality measurements, morphological observations, reproductive biology assessments, and laboratory analysis of condition factor. The results showed that P. partipentazona exhibited gonadal maturity stages (GMS) I - IV. The female gonadosomatic index (GSI 0,046 – 0,090%) was higher than that of males (0,006 – 0,020%) at all stations. The length at first maturity was greater in females (47,58 – 56,89 mm) than in males (42,81 – 46,13 mm). Fecundity ranged from 194 - 361 eggs and was positively correlated with body length and weight. Sexual dimorphism was observed in body coloration and shape. The condition factor ranged from 0,97 – 1,32, indicating good physiological condition and a favorable environment for growth and reproduction. These findings indicate a high adaptive potential of P. partipentazona in the Lake Toba ecosystem.